1988
DOI: 10.1111/j.1476-5381.1988.tb11745.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects and interactions of sensory neuropeptides on airway microvascular leakage in guinea‐pigs

Abstract: 1 We have studied the effect of the sensory neuropeptides substance P (SP), neurokinin A (NKA), neurokinin B (NKB) and calcitonin gene-related peptide (CGRP) on microvascular permeability in guinea-pig airways in vivo and investigated whether CGRP would potentiate the effect of SP. We used the extravasation of intravenously-injected Evans blue dye as an index of permeability. 2 The tachykinins SP, NKA and NKB (0.025-5.Onmol kg-, i.v.) significantly (P <0.05) increased extravasation of dye in a dose-related man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 38 publications
5
64
1
1
Order By: Relevance
“…Cholinergic mechanisms contribute little or nothing to airway plasma leakage whereas NANC neural mechanisms potently induce airway exudation in rodents . This 'neurogenic' plasma exudation can be blocked in a number of ways including the use of anaesthetics such as Hypnorm which contain opiates (Belvisi et al, 1988). Animals anaesthetized with Hypnorm should exhibit reduced leakage in response to bradykinin compared with those anaesthetized with urethane, a nonopioid containing anaesthetic, when the anti-leakage effects of urethane-induced release of endogenous catecholamines (Spriggs, 1965) are blocked by adrenoceptor antagonists (Boschetto et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic mechanisms contribute little or nothing to airway plasma leakage whereas NANC neural mechanisms potently induce airway exudation in rodents . This 'neurogenic' plasma exudation can be blocked in a number of ways including the use of anaesthetics such as Hypnorm which contain opiates (Belvisi et al, 1988). Animals anaesthetized with Hypnorm should exhibit reduced leakage in response to bradykinin compared with those anaesthetized with urethane, a nonopioid containing anaesthetic, when the anti-leakage effects of urethane-induced release of endogenous catecholamines (Spriggs, 1965) are blocked by adrenoceptor antagonists (Boschetto et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously (Belvisi et al, 1988) that leakage due to the non-adrenergic, non-cholinergic (NANC) component of vagus nerve stimulation is significantly attenuated with diazepam-Hypnorm: leakage under urethane anaesthesia should be relatively greater. To prevent urethane-induced release of endogenous catecholamines reducing the magnitude of leakage (Boschetto et al, 1988), phentolamine (2.5mg kg-1) and propranolol (1 mgkg-1) were given i.v.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Há outros corantes, além do azul de Evans, que se ligam à albumina, como o azul Celeste de Niágara, o azul Celeste de Pontamina 6BX e o azul de Tripan (2,(10)(11)(12)(13)(14)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . O azul de Evans é um corante capaz de ser mensurável por meio de espectrofotometria (11)(12) .…”
Section: Introductionunclassified
“…These tachykinins can cause several pathological effects in the airways, including airway smooth muscle contraction, mucus secretion and increased microvascular permeability (Nilsson et al, 1977;Andersson & Persson, 1977;Saria et al, 1983;Hua et al, 1984;Coles et al, 1984;Rogers et al, 1988;Lotvall et al, 1990a). It has also been shown that inhaled NKA, but not SP, causes airway narrowing in asthmatic patients, but not in non-asthmatics (Joos et al, 1986;Fuller et al, 1987).…”
Section: Introductionmentioning
confidence: 99%